Estimasi Angka Partisipasi Kasar Perguruan Tinggi Level Kabupaten/Kota di Pulau Kalimantan Tahun 2020 dengan Small Area Estimation Hierarchical Bayes Beta-Logistic - Nugraheni Putri Istiqomah; Ika Yuni Wulansari (Politeknik Statistika STIS, 2022)
Improving quality of education is not only a national agenda, but also a priority of international agenda. Based on Susenas March 2020, higher education has lowest Gross Enrollment Rate (GER) compared to other education levels. Kalimantan has the lowest GER of higher education in 2020. Small area statistics urgently needed to reach more right on target policies. Although Susenas March 2020 is designed to present estimates up to regency or city level, the Relative Standard Error (RSE) several regencies/cities which is more than 25% indicates that the direct estimator has insufficient precision. Therefore, this study applies indirect estimation using Small Area Estimation (SAE) with the method of Empirical Best Linear Unbiased Predictor (EBLUP) and Hierarchical Bayes Beta-logistic (HB Beta-logistic) to improve the precision of the direct estimator. The results showed that HB Beta-logistic estimator was the most precise estimator compared to direct estimator and EBLUP estimator.